Existence and Controllability Results for Fractional Impulsive Integrodifferential Systems in Banach Spaces. (10th June 2013) - Qin, Haiyong; Zuo, Xin; Liu, Jianwei
Abstract : We firstly study the existence of PC-mild solutions for impulsive fractional semilinear integrodifferential equations and then present controllability results for fractional impulsive integrodifferential systems in Banach spaces. The method we adopt is based on fixed point theorem, semigroup theory, and generalized Bellman inequality. The results obtained in this paper improve and extend some known results. At last, an example is presented to demonstrate the applications of our main results.